Analysis of the Role of Sport in the Changing Status of Graffiti - Kisung Kwon; Jeehyun Kang (Korea Institute of Sport Science, 2022)
PURPOSE Although sport and graffiti often collaborate in various forms and sectors, research on this phenomenon is insufficient. Therefore, this exploratory study analyzed the role of sport in line with the diffusion of graffiti in Korea. METHODS Qualitative research method was applied for data collection and analysis. Specifically, systematic literature review, semi-structured in-depth interviews, and written interviews were used for data collection. Subsequently, content analysis, categorization, and itemization were performed. RESULTS International sporting events had an impact on the diffusion process of graffiti. Additionally, graffiti was used as a promotional content for sporting events and sport brands, and specific sport content were used as the medium for street art works, including graffiti. Furthermore, graffiti was used as a promotional content for marketing activities in collaboration with a professional sports team by general corporations. CONCLUSIONS As graffiti becomes one of the major cultures from a subculture, it is expected to increase public interest in all sports and not just in specific sports through collaboration with graffiti.